Implementation of MQTT Protocol for Artificial Intelligence - Khot, Suraj; Mali, Abhijeet (International Journal of Engineering and Management Research, 2024)
The IoT-Based Attendance Management System is a sophisticated solution leveraging Azure services and MQTT protocol for efficient attendance tracking. The system comprises a Face Device equipped with facial recognition capabilities, which captures attendance data and communicates with Azure IoT Hub. The Azure IoT Hub, acting as the central hub, receives and processes attendance data from the face device, utilizing MQTT for real-time communication. A dedicated MQTT service, facilitated by the Mosquitto broker, subscribes to the Azure IoT Hub, ensuring seamless data flow between the face device and the broader system. The web application, hosted on Azure App Service and integrated with SQL Server, serves as the user interface. It not only interacts with the face device through Azure IoT Hub but also processes attendance data and generates comprehensive reports, enhancing the overall efficiency of attendance management through the power of IoT. This architecture offers a scalable, secure, and real-time attendance management solution, bridging the physical and digital realms through facial recognition technology and Azure IoT services. The synergy of components, from the MQTT-enabled face device to the Azure-based web application, establishes a robust ecosystem for capturing, processing, and presenting attendance data with seamless integration and reliability.